2017
DOI: 10.1016/j.catena.2016.03.042
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reservoirs on streamflow and river regimes in a heavily regulated river basin of Northeast Spain

Abstract: Dams modify downstream hydrology because they alter natural river regimes and divert river flows. The Segre Basin is one of the main tributaries of the Ebro River in Northeastern Spain, and has a drainage area of 13,000 km 2. In this study, we used data on long-term (1951-2013) river flows and climatic series to analyze the downstream cumulative effect of dams on natural river regimes and the disassociation between changes in climate and runoff in the Segre Basin. The headwaters of this basin are in the Pyrene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 51 publications
2
25
0
Order By: Relevance
“…In these water bodies, the water evaporated is enhanced as a response to an increased AED (Friedrich et al, ; Martínez‐Granados, Maestre‐Valero, Calatrava, & Martínez‐Alvarez, ). If regulated water in reservoirs is used for irrigation, there is an important indirect hydrological effect of the AED as a consequence of enhanced ET in cultivations (Porter & Semenov, ), and subsequent decrease of the water returns to the river courses (Vicente‐Serrano, et al, ), increasing hydrological droughts downstream (Vicente‐Serrano et al, ).…”
Section: The Complex Influence Of Aed On Drought Severitymentioning
confidence: 99%
“…In these water bodies, the water evaporated is enhanced as a response to an increased AED (Friedrich et al, ; Martínez‐Granados, Maestre‐Valero, Calatrava, & Martínez‐Alvarez, ). If regulated water in reservoirs is used for irrigation, there is an important indirect hydrological effect of the AED as a consequence of enhanced ET in cultivations (Porter & Semenov, ), and subsequent decrease of the water returns to the river courses (Vicente‐Serrano, et al, ), increasing hydrological droughts downstream (Vicente‐Serrano et al, ).…”
Section: The Complex Influence Of Aed On Drought Severitymentioning
confidence: 99%
“…The number of reservoirs have increased dramatically over the past several decades, reaching about 16.7 million dams and over 50,000 large dams in the current world [16]. Undoubtedly, these dams have the potential to disrupt the original geochemical processes and ecological connectivity of rivers [16,17]. Based on the geographical distribution from the river to reservoir, river-reservoir systems are commonly used to describe its hybrid environmental properties.…”
Section: Introductionmentioning
confidence: 99%
“…The results show that: (1) the reservoir has a delay and reduction effect on the flood during the flood season, and has a replenishment effect on the runoff during the dry season; (2) the impact of the reservoir on runoff processes and changes in runoff distribution during the year increases with the reservoir capacity; (3) the mitigation of flooding is more obvious at the river basin outlet control station when the reservoir is further downstream; (4) an arrangement with the smaller reservoir located upstream and the larger reservoir located downstream can maximize the benefits of the reservoirs in flood control.The long-term trend of interannual variation in runoff downstream of the reservoir does not appear to be related to long-term climate change, as there was no correlation (or very weak correlation) between the flow downstream of the reservoir and the climate variables (precipitation and temperature) [6]. The results of Vicente-Serrano et al [7] showed that the gradual increase of reservoir capacity in the basin complicated the non-linear correlation between precipitation and runoff, and that the reservoir could lead to a significant decline in runoff downstream and also to significant changes to the natural river conditions. One of the main hydrological effects of the reservoirs on runoff was a reduction of runoff variation, and uniformity of flow, which was due to the decrease in peak flow and the enhancement of minimum flow [8].…”
mentioning
confidence: 82%
“…The long-term trend of interannual variation in runoff downstream of the reservoir does not appear to be related to long-term climate change, as there was no correlation (or very weak correlation) between the flow downstream of the reservoir and the climate variables (precipitation and temperature) [6]. The results of Vicente-Serrano et al [7] showed that the gradual increase of reservoir capacity in the basin complicated the non-linear correlation between precipitation and runoff, and that the reservoir could lead to a significant decline in runoff downstream and also to significant changes to the natural river conditions. One of the main hydrological effects of the reservoirs on runoff was a reduction of runoff variation, and uniformity of flow, which was due to the decrease in peak flow and the enhancement of minimum flow [8].…”
mentioning
confidence: 82%